Xanthogranulomatous Pyelonephritis: Analysis of 18 Cases - Mohammed Ahmed Al-Ghazo; Ibrahim Fathi Ghalayini; Ismail Ibrahim Matalka; Nabih Shaker Al-Kaisi; Yousef Saleh Khader (Asian Journal of Surgery, 2006)
To review and evaluate patients with a clinicopathological diagnosis of xanthogranulomatous pyelonephritis (XGP) with emphasis on the diagnostic methods and the effect of socioeconomic status on disease severity. Methods: Data compiled from the previous history of the patients, clinical, laboratory, radioimaging findings, preoperative, operative, histopathological diagnosis and postoperative follow-up period were analysed. On the basis of presentation, XGP was classified as complicated and simple. Results: There were 18 cases of XGP. The clinical characteristics included: calculi or obstruction in the urinary tract, and damage to the kidney, complication of urinary tract infection, anaemia, increased erythrocyte sedimentation rate and liver dysfunction. All patients had diffuse XGP. Associated pathological findings such as psoas abscess, nephrocutaneous fistula, renocolonic fistula and paranephric abscess were found in 33.3% of cases. Eleven of 14 patients (78.6%) who were evaluated by computed tomography (CT) had the correct diagnosis made prior to nephrectomy. Urine culture was positive in 88.9% of patients and Proteus mirabilis was the most common organism. Conclusion: Our experience with a small number of patients demonstrates that low socioeconomic status could be a risk factor in the development of complicated cases of XGP. CT is considered to be the best radiological test for correct preoperative diagnosis and evaluation of XGP. Nephrectomy and removal of all surrounding affected tissue proved to be curative for XGP.